Long-Term Storage Quality of Table Grapes as Influenced by Pre-Harvest Yeast Applications and Post-Harvest Use of Controlled Atmosphere - Klaasen, Jeremy A.; van der Merwe, Jacobus A.; Vries, Filicity. A.; Calitz, Frederick J. (South African Journal of Enology and Viticulture, 2017)
The effects of pre-harvest applications of antagonistic yeast and controlled atmosphere storage treatments on inhibiting Botrytis cinerea decay and maintaining the quality of table grapes were compared to identify a treatment that could replace the use of sulphur dioxide (SO2) during post-harvest handling. Treatments for this study included pre-harvest application of antagonistic yeasts Cryptococcus albidus (Yieldplus®), Cryptococcus sp. (LF) and Candida pelliculosa (R951) on table grapes (cvs. ‘Barlinka’, ‘Dauphine’, ‘Red Globe’, ‘Sunred Seedless’ and ‘Thompson Seedless’) from 2001 to 2003. Grapes were stored under regular (air), controlled atmosphere (CA, O2 + CO2) and SO2 conditions at -0.5°C and subsequent storage at a 15°C to simulate shelf-life conditions. Results of this study showed that Botrytis decay levels did not develop rapidly due to low temperatures (-0.5°C vs 15°C), shorter storage periods (4 vs 8 weeks or 0 vs 7 vs 14 days), and CA treatment effects. The CA gas mixtures maintained commercially important low levels (less than 1%) of B. cinerea decay during the cold storage period at -0.5°C. However, during shelf-life storage at 15°C these low levels of decay could only be maintained by some of the SO2 treatments. A necessary commercial requirement is to maintain low decay levels for longer at higher shelf-life temperatures, for which this study cannot conclusively recommend a CA and/or antagonistic yeast treatment as an alternative to SO2. However, pre-harvest applications of the yeast and CA limited the general quality deterioration of the grapes at -0.5°C and 15°C compared to SO2 treatments. Inclusion of macro- or micro-perforated polyethylene packaging liners in combination with CA and pre-harvest yeast treatments did not show obvious negative effects on quality parameters in this study. Discovery and selection of yeast strains that survive under low temperatures and CA conditions would make suitable candidates for continued control of decay development on the fruit surface during shelf-life storage periods.